Comparative assessment of mangrove and non-mangrove-based shrimp farming systems in Ayeyarwaddy delta, Myanmar - Kyaw Moe Oo; Salin, Krishna R.; Bhujel, Ram C.; Sasaki, Nophea; Russell E. Train Education for Nature Program World Wildlife Fund, Inc. (WWF) (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Mangrove forests provide severalecosystem services and are of great economic value. Mangrovesplay avital rolein maintaining theecology ofcoastal zonesand support aquatic diversity with many of the coastal fauna dependingon mangrove ecosystem during part or wholeof theirlife cycles. Since2002,extensive areas of mangrove forests have been developedfor shrimp farmingin Ayeyarwaddy delta, Myanmar leading to huge loss of mangrove biodiversity. To rehabilitate the massive loss of mangrove foreststhat have occurredas a consequence of shrimp farm development, severalreforestation activities werecarried out in Ayeyarwaddy delta. However,these efforts werenot always successful because there were recurrentconflicts of using those areas for human settlement, agriculture and aquaculture. To resolve these problems, mangrove-based shrimp farming systemwasintroducedin Pyapon Township since 2014.In the present study, the two shrimp farming systems, viz., mangrove-based,and non-mangrove-based(conventional) farming systems were evaluatedin threetownships in the Ayeyarwaddy delta region. The study was conducted by a field survey to compare the technical and economic efficiency ofeach shrimp farming system, and by interviews with key stakeholderstoevaluate farmer perception onthetwo farming systems regardingsocial, technical, economic and environmental aspects. Evaluation of the technical efficiency of the farming systems revealed that the variationsin shrimp yield in the mangrove-based system were attributable to the differences in stocking density, stocking period, water spread area, presence of sluice gates, pond preparation(drying), water exchange, water levelin fields, and farmers'education level and experience.In mangrove-basedand non-mangrove basedshrimp systems,theshrimp yield was positively correlatedwith stocking density. In the former,the number of sluice gateswas also found to have a significant effect on yield. Although the shrimp yields from mangrove-based farms were marginally higher than non-mangrove shrimp farms, these difference were not significant. Apart from the shrimp harvested, the mangrove-based farming system was benefittedby an additional production of crab and fish contributing to the total farm yield. The study has also evaluatedthe benefits, problems,and constraints of farmers who are involved in both mangrove-based and conventional shrimp farming systems.Thecost of production was found to be lower inthemangrove-based system.Thenet income, return on investment and benefit-costratio werealso higher in mangrove-based than non-mangrove-based shrimp farming system. The resultsshowed that mangrove-based shrimp farming system hasabetter technical and economic efficiency compared to non-mangrove shrimp farming systems. Thisis an important finding that supports the perceived potential thatmangrove ecosystems couldcontribute tosocio-economic development of the dependent communitiesby capitalizing ontheirecosystem services, while these could also support traditional, yet successful aquaculture ventures. The study has also providedtherecommendations that would enable an appropriate institutional framework byadopting better management practices inmangrove-based shrimp farming systemsin Myanmar.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Mangrove forests -- Economic aspects -- Myanmar -- Ayeyarwaddy delta; Shrimp culture -- Economic aspects -- Myanmar -- Ayeyarwaddy delta